Iron-Catalyzed Oxidative Coupling Reaction of N-Acyl Glycine Esters and Malonates - Yu, Hui; Liu, Zhongyang; Lin, Jingbo (Synlett, 2016)
An iron-catalyzed direct C–C double-bond formation process is described in this paper. Using DTBP as the oxidant and FeCl3·6H2O (20 mol%) as the catalyst, N-2-pyridinecarbonyl glycine esters were coupled with malonates to provide amido acrylates in moderate to good yields. A possible reaction pathway for the formation of the products is also discussed in this paper.
Keywords: iron catalysis; glycine esters; malonates; DTBP; oxidative coupling